Implante percutáneo de válvula aórtica con apoyo de circulación extracorpórea en paciente con insuficiencia aórtica severa - Martínez,Gonzalo (Sociedad Chilena de Cardiología y Cirugía Cardiovascular, 2017)
An 84-year man with prior coronary artery bypass surgery and endovascular repair of an abdominal aortic aneurysm developed congestive heart failu-re. He had calcific aortic valve disease with severe regurgitation. A #29 Edwards-Sapien aortic valve via trans-apical approach was implanted with the patient connected to extra corporeal circulation. The patient recovered successfully and remained in functional class II 8 months after hospital dis-charge.